Histologic and Endoscopic Similarity between Nodular Gastric Antral Vascular Ectasia and Gastric Hyperplastic Polyps Potentially Causing Treatment Delays - Pujitha Kudaravalli; Sheikh A. Saleem; Rachana Mandru; Sekou Rawlins (Case Reports in Medicine)
Introduction. Gastric antral vascular ectasia (GAVE) is the underlying cause for 4% of nonvariceal upper GI bleeding. Nodular GAVE and gastric hyperplastic polyps have similar appearance on upper GI endoscopy (EGD) as well as histology, which could delay specific targeted therapy. We herein, through this case, would like to highlight that high clinical suspicion is required to diagnose nodular GAVE. Case Report. A 70-year-old male with a past medical history significant for coronary artery disease s/p drug-eluting stent placement on Plavix, coronary artery bypass grafting, mechanical aortic valve replacement on warfarin, and iron deficiency anemia on replacement was admitted for the evaluation of fatigue and melena for a month. Physical examination was positive for black stool. The only significant lab was a drop in hemoglobin/hematocrit (Hg/dl/H%) of 10/32 to 4/12.5. Fibrosure was sought which suggested that the patient had an F4 cirrhosis. Endoscopy showed nodules in the gastric antrum which were presumptively treated as GAVE with argon plasma coagulation (APC). Surgical pathology showed reactive gastropathy and gastric polyps. Review of the past histology suggested that because of the overlap in the histopathological features of hyperplastic polyps and GAVE, they were misinterpreted as hyperplastic polyp rather than nodular GAVE. Discussion. GAVE can be classified endoscopically as punctate, striped, nodular, or polypoidal form. The light microscopic findings considered specific to GAVE are vascular hyperplasia, mucosal vascular ectasia, intravascular fibrin thrombi, and fibromuscular hyperplasia. However, these findings do not differentiate GAVE from hyperplastic gastric polyp. The first line of treatment for GAVE is endoscopic ablation with Nd:YAG laser or argon plasma coagulation. Response to therapy was seen with a mean of 2.6 treatment sessions. There is not a lot of evidence supportive of pharmacological treatment of GAVE with estrogen-progesterone, tranexamic acid, and thalidomide. Serial endoscopic band ligation as well as detachable snares in the management of nodular GAVE refractory to argon plasma coagulation has also been tried. Conclusion. Oftentimes, there is a delay in the diagnosis and treatment of nodular GAVE as the histopathological appearance could be similar to gastric polyps. The diagnosis of GAVE especially nodular GAVE requires a high level of clinical suspicion. Misdiagnosis of nodular GAVE can delay targeted therapy and have fatal outcomes.